Determinants of dividend policy in banking sector: evidence from Malaysia / Fatin Aqiila Ruslan - Ruslan, Fatin Aqiila (2019)
This paper has been studied to investigate which factors will influence the dividend policy in banking sector evidence from Malaysia. Panel data were used in this study that cover the twenty years of period from 1998 until 2017 that has been comprised of eight commercial banks listed in Bursa Malaysia. All the data collected by yearly and had been analysed by using the framework of fixed effect model. The result shows that firm size (Size), leverage (LEV) and dividend yield (DY) have positively significant relationship with the dependent variable, dividend payout (DP). However, profitability (P) had a positive relationship but the result is insignificant with the dividend payout. In all, the future researchers need to study the factor influence the dividend policy by using others variables with a long period of time in order to obtain the relationship between the dividend payout.